Evaluation of the Metabolizable Energy of Meat and Bone Meal for Chickens and Turkeys by Various Methods - Robbins, D.H.; Firman, J.D. (International Journal of Poultry Science, 2005)
A series of assays were conducted to determine to the available energy of several meat and bone meal products by various methods. The correct determination of the energy available to poultry from these products is important for accurate diet formulation and product usage. Several methods for determining energy availability are utilized, including true metabolizable energy (TME) and excreta and digesta apparent metabolizable energy (AME). The goal of these experiments was to determine if any differences exist among the available energy values determined by the various methods. There were few differences in assay methodologies noted. There were significant differences in mean ME values among products, as would be expected due to meat and bone meal`s variable nature. Chick digesta AME values were usually the only cause of difference, typically lower than other values. There were no differences between pooled AME and TME values, or between chickens and turkeys. In general, it appears that the TME values commonly determined with Leghorn roosters are acceptable for broilers and turkeys. The proximate analysis and mineral composition values of the meat and bone meal products were also determined. These values were then used to develop equations that predict the TMEn of a product. The products were too variable to provide an accurate equation using the proximate values (R2 = 0.42). Using the gross energy of the product as a predictor variable greatly improved the accuracy, with an R2 of 0.77.